Effect of Chest Drain Management Guidelines on Knowledge and Practice Among Nurses at Services Hospital : Chest Drain Management Guidelines on Knowledge Among Nurses - Kouser, Shehnaz; Ali, Afsar; Yaqoob, Adnan (Pakistan Journal of Health Sciences, 2023)
Chest drain are inserted to help treat various conditions like pneumothorax, empyema and pleural effusion etcetera. It is also very much indicated after chest trauma and thoracic surgeries. Objective: To determine the effect of chest drain management guidelines on knowledge and practices among Nurses at Services Hospital Lahore, Pakistan. Methods: One group Pre-post quasi experimental design was used. The study was conducted from December 2021 to April 2022 at the thoracic surgery, medical and surgical ICUS department of services hospital Lahore, Pakistan. Thirty-six registered nurses were selected by convenience sampling from services hospital Lahore according to inclusion and exclusion criteria. Data was collected from the participants by adopted, valid, and reliable tools. A structured questionnaire was used to evaluate the pre-post data that contained 25 true false-based knowledge questions and checklist containing 13 items were used to assess the level of practice of nurses before and after guidelines-based educational intervention. Results: The results revealed a positive effect of educational guidelines on improving the knowledge and practice of nurses about chest drain management with Mean ± S.D(8.83±1.69; 19.08 ±2.53) (4.92±1.73; 10.97±0.74) in post-test respectively with statistically significant p-value (p-value <0.001). Conclusions: The education of nurses by educational guidelines have a significant effect on improving nurses’ knowledge and practice about chest drain management.